Peran Kepemimpinan Kepala Sekolah dalam Meningkatkan Kinerja Guru di SMP Islam Terpadu Babunnajah Menes - Rasad Mulyadi; Anis Fauzi; Anis Zohriah (Departement of Mathematics Education, 2023)
The principal's administration can influence school activities. This research uses qualitative research and describes the problems studied. This type of research uses qualitative research to identify and describe the role of the principal in improving teacher performance at SMP IT Babunjah Menes. Therefore this type of site-based research is field research where researchers go directly to the field to see firsthand what the purpose of the research is. Qualitative research has three data collection techniques, namely interviews, documentation and observation. Based on the results of this study, there are two things that are in line with the problems that the researchers found, including 1). The principal as a leader can motivate and direct stakeholders to work well in accordance with the school's vision and mission to improve teacher performance. 2). Principal management as a leader provides evaluations to increase teacher effectiveness in advancing schools 3). Among other things, the big role of the school principal in implementing the management process and managing it appropriately according to the work program that has been prepared to produce the best results, greatly influences the change and improvement of teacher performance. school. very good results. The role of the principal in providing directions in improving teacher performance has been fulfilled, but not all of them have increased greatly.